Beyond our differences [videorecording (DVD)] - Bisanz, Peter; Bisanz, Peter; Bisanz, Peter (PBS Home Video, 2009)
Features interviews with religious leaders and politicians as they are asked what inspires them in these challenging times, as more and more people are turning to religion and spirituality to gain a sense of meaning and understanding with what they are facing.